TRANSFORMASI SYAIR DODAIDI: DARI TRADISI LISAN KE KOMERSIALISASI DIGITAL DALAM SEJARAH MASYARAKAT ACEH - Haikal, Haikal; Nurhayati, Anifa (UI Scholars Hub, 2025)
Syair Dodaidi, as a form of Acehnese oral tradition, has played a significant role in the social and cultural life of the Acehnese people for centuries. It originally developed as a lullaby sung by mothers to their children, with lyrics containing prayers and praise to Allah SWT. This study aims to examine the transformation of Syair Dodaidi in the context of contemporary Acehnese society. The research methodology uses a historical approach with the stages of heuristics, source criticism, interpretation, and historiography. The results show that although Syair Dodaidi is still practiced as part of cultural heritage, there have been a number of transformations in the way the poem is maintained and presented en masse. The study observed changes in medium and presentation, but the values contained in Syair Dodaidi - such as character education, spirituality and cultural identity - remain relevant and valued by the people of Aceh. The study reveals that Syair Dodaidi is able to adapt to the contemporary era while maintaining its traditional essence, making it an interesting example of how oral traditions can survive and thrive in the face of changing times